2020
DOI: 10.3389/fmed.2020.568350
|View full text |Cite
|
Sign up to set email alerts
|

Older Age and High Serum Ferritin Levels Associated With the Risk of Chronic Cytopenia in Hemodialysis Patients

Abstract: Leukopenia or thrombocytopenia is sometimes observed in end-stage renal disease (ESRD) patients, but the association between chronic leukopenia or thrombocytopenia and hemodialysis (HD) is still unclear. We aimed to investigate the incidence of chronic leukopenia or thrombocytopenia in patients with ESRD who received HD and to determine the risk factors of this complication. We retrospectively analyzed ESRD patients treated with HD at Ditmanson Medical Foundation Chia-Yi Christian Hospital in 2018. The risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…The results of the current study showed in the age group (40-60) that there was an increase significant at (P< 0.05) in WBC for hemodialysis patients compared with control According to the table indicated (1-1). That's agreement with previous studies [15]. The results of the current study showed in the age group (40-60) that there was an increase significant at (P< 0.05) in WBC for non-hemodialysis patients compared with control According to the table indicated (1).…”
Section: Parameter Of Bloodsupporting
confidence: 92%
“…The results of the current study showed in the age group (40-60) that there was an increase significant at (P< 0.05) in WBC for hemodialysis patients compared with control According to the table indicated (1-1). That's agreement with previous studies [15]. The results of the current study showed in the age group (40-60) that there was an increase significant at (P< 0.05) in WBC for non-hemodialysis patients compared with control According to the table indicated (1).…”
Section: Parameter Of Bloodsupporting
confidence: 92%
“…First, this was a small, single-center retrospectively designed cohort, so selection bias was inevitable. For example, patients who refused PTX were elderly and fragile and were not enrolled [ 15 , 18 ]. Second, we lacked bone marrow and cytogenetic data to measure the degree of bone marrow fibrosis and examine myelodysplastic syndrome, a hematopoietic disease.…”
Section: Discussionmentioning
confidence: 99%
“…PTX has been reported to improve anemia and reduce the dose of ESA in patients with SHPT, but these data were not consistent [ 12 , 13 , 14 ]. In addition, our previous study suggested that chronic cytopenia was a consequence of long-term hemodialysis but PTX did not reverse or affect the patients’ hematologic profile [ 15 ]. We proposed that this insignificance could be attributed to heterogeneous entities in ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory state/chronic inflammatory microenvironment is considered a consequence, a trigger, and/or an aggravating factor for the diseases mentioned above, leading to increased patient morbidity and mortality rates and the development of other severe chronic diseases [30 36-39]. Older age and male patients usually have higher serum ferritin levels than younger and female counterparts [40][41][42][43][44][45]. An elevated serum ferritin level in such diseases is considered an inflammatory marker, an acute phase reactant.…”
Section: Increased Serum Ferritin Levels In Diseasesmentioning
confidence: 99%